2018
DOI: 10.3390/ijms19020368
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-Actin Crosslinking Factor 1 and Plakins as Therapeutic Drug Targets

Abstract: Plakins are a family of seven cytoskeletal cross-linker proteins (microtubule-actin crosslinking factor 1 (MACF), bullous pemphigoid antigen (BPAG1) desmoplakin, envoplakin, periplakin, plectin, epiplakin) that network the three major filaments that comprise the cytoskeleton. Plakins have been found to be involved in disorders and diseases of the skin, heart, nervous system, and cancer that are attributed to autoimmune responses and genetic alterations of these macromolecules. Despite their role and involvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 111 publications
0
12
0
Order By: Relevance
“…K2209 of MACF1 was also cross-linked to two sites in the middle domain of HS90B. Although not a direct target of PTX, MACF1 has been shown to be indirectly affected and differentially responsive to MT-targeting drugs (Quick, 2018). MACF1 is associated with several diseases, including cancer, suggesting it could be a useful therapeutic target for future drug development (Afghani et al, 2017; Miao et al, 2017; Quick, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…K2209 of MACF1 was also cross-linked to two sites in the middle domain of HS90B. Although not a direct target of PTX, MACF1 has been shown to be indirectly affected and differentially responsive to MT-targeting drugs (Quick, 2018). MACF1 is associated with several diseases, including cancer, suggesting it could be a useful therapeutic target for future drug development (Afghani et al, 2017; Miao et al, 2017; Quick, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Although not a direct target of PTX, MACF1 has been shown to be indirectly affected and differentially responsive to MT-targeting drugs (Quick, 2018). MACF1 is associated with several diseases, including cancer, suggesting it could be a useful therapeutic target for future drug development (Afghani et al, 2017; Miao et al, 2017; Quick, 2018). AHNK2 is an oncogenic protein and prognostic marker in several carcinomas, including pancreatic ductal adenocarcinoma (PDAC), a highly aggressive and malignant disease that is currently the fourth-leading cause of cancer deaths worldwide (Bhasin et al, 2016; Garrido-Laguna and Hidalgo, 2015; Klett et al, 2018; Lu etal., 2017; Wang etal., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…As the downregulation of desmoplakin has been found in OSCC [ 133 ] ( Table 2 ), the finding of Lorch et al suggests desmoplakin as a potential target for cancer therapy. More recently, Quick, by using the Research Collaboratory for Structural Bioinformatics (RCSB) protein data bank, has identified several anticancer drugs that interact with BPAG1, MACF1, and plectin [ 143 ]. Ibrutinib is one common ligand for both BPAG1 and MACF1, and is used clinically for the treatment of lymphoma and leukemia [ 144 , 145 ].…”
Section: Mammalian Plakins In Human Cancermentioning
confidence: 99%
“…The association between BP and neurodegenerative diseases is well-described ( 11 , 12 ). There is evidence that having a neurodegenerative disease increases the risk for developing BP and that patients with neurodegenerative diseases have a higher standardized mortality rate.…”
Section: Bullous Pemphigoid and Neurological Diseasementioning
confidence: 99%
“…A new publication by Quick et al elucidates BP antigens as potential targets in future therapy of patients with BP ( 11 ).…”
Section: Treatment Of Bullous Pemphigoidmentioning
confidence: 99%